Understanding plastome evolution in Hemiparasitic Santalales: Complete chloroplast genomes of three species, Dendrotrophe varians, Helixanthera parasitica, and Macrosolen cochinchinensis. - Hye Woo Shin; Nam Sook Lee (PLoS ONE)
Santalales is a large order, with over 2200 species, most of which are root or aerial (stem) hemiparasites. In this study, we report the newly assembled chloroplast genome of Dendrotrophe varians (140,666 bp) in the family Amphorogynaceae and the cp genomes of Helixanthera parasitica (124,881 bp) and Macrosolen cochinchinensis (122,986 bp), both in the family Loranthaceae. We compared the cp genomes of 11 Santalales including eight currently available cp genomes. Santalales cp genomes are slightly or not reduced in size (119-147 kb), similar to other hemiparasitic species, when compared with typical angiosperm cp genomes (120-170 kb). In a phylogeny examining gene content, the NADH dehydrogenase gene group is the only one among eight functional gene groups that lost complete functionally in all examined Santalales. This supports the idea that the functional loss of ndh genes is the initial stage in the evolution of the plastome of parasitic plants, but the loss has occurred independently multiple times in angiosperms, while they are not found in some parasites. This suggests that the functional loss of ndh genes is not essential for the transition from autotroph to parasite. We additionally examined the correlation between gene content and type of parasitism (obligate/facultative and stem/root parasites) of all hemiparasitic species in which cp genomes have been reported to date. Correlation was not found in any types of parasitism.